1990
DOI: 10.1152/jappl.1990.68.3.1177
|View full text |Cite
|
Sign up to set email alerts
|

Electromyogram power spectra frequencies associated with motor unit recruitment strategies

Abstract: The isolated contributions of motor unit recruitment and firing rate variations to the median frequency of the electromyogram's power density spectrum were determined. Orderly stimulation of the cat gastrocnemius motor units via nerve electrodes gave rise to linearly increasing median frequency regardless of the action potential firing rate of the active motor units. Increase in the discharge rate of all the motor units resulted in nearly constant median frequency. It was concluded that the increasing average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
140
3
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(164 citation statements)
references
References 0 publications
11
140
3
5
Order By: Relevance
“…The limitations discussed in the preceding paragraph are sometimes considered to be negligible (26). A study often cited to support this assertion is the observation by Solomonow et al (23) that orderly stimulation of motor units in the cat gastrocnemius muscle via nerve electrodes gave rise to linearly increasing median frequency of the intramuscular EMG signal. As noted by the authors, however, "attempts to extend the findings .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations discussed in the preceding paragraph are sometimes considered to be negligible (26). A study often cited to support this assertion is the observation by Solomonow et al (23) that orderly stimulation of motor units in the cat gastrocnemius muscle via nerve electrodes gave rise to linearly increasing median frequency of the intramuscular EMG signal. As noted by the authors, however, "attempts to extend the findings .…”
mentioning
confidence: 99%
“…. to data obtained from voluntary contractions require the consideration of several secondary but not unimportant factors" (23). These factors, which are common to other animal studies (17,28), include differences between electrically evoked EMG signals and those detected during voluntary contractions, intramuscular (or over the muscle fascia) and surface recordings, and recordings of activity by discrete and mixed populations of muscle fiber types.…”
mentioning
confidence: 99%
“…The effect of the firing rate, however, appears only in the low frequency range (0-40 Hz), so the MNF and MDF methods are weakly dependent on the firing rate 16,17 . Previous theoretical 17,18 and experimental 19 studies report that although the firing statistics of active MUs were changed, they do not significantly affect the MNF and MDF.…”
Section: Introductionmentioning
confidence: 87%
“…Our previous study results indicated that the measurement of back muscle fatigability, especially the erector spinae muscle, indicated that the entropy analysis was a more reliable measure than the power spectral analysis (Sung et al, 2008b). It is well known that the observed EMG signal depends on anatomical factors, such as muscle geometry, subcutaneous fat, gender, and other confounding factors (Lindstrom et al, 1974;Mannion et al, 1997c;Pullman et al, 2000;Roy et al, 1997;Solomonow et al, 1990). As a result, observed quantities from EMG signals show considerable variations even among a group of healthy subjects.…”
Section: Reliability Of Surface Electromyography Analysismentioning
confidence: 97%